2023
DOI: 10.1186/s11658-023-00463-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel tyrosine tRNA-derived fragment, tRFTyr, induces oncogenesis and lactate accumulation in LSCC by interacting with LDHA

Abstract: Background Transfer (t)RNA-derived small RNA (tsRNA), generated from precursor or mature tRNA, is a new type of small non-coding RNA (sncRNA) that has recently been shown to play a vital role in human cancers. However, its role in laryngeal squamous cell carcinoma (LSCC) remains unclear. Methods We elucidated the expression profiles of tsRNAs in four paired LSCC and non-neoplastic tissues by sequencing and verified the sequencing data by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…These complexes are then transported to the nucleus, enhancing the interaction between EEF1A1 and the MDM2 proto-oncogene (MDM2), ultimately promoting GC progression [ 49 ]. Additionally, Zhao et al [ 50 ] found that the upregulated tRF-Tyr in laryngeal squamous cell carcinoma enhances tumor progression by binding with lactate dehydrogenase A (LDHA), affecting its phosphorylation and leading to increased lactic acid accumulation [ 50 ]. These studies highlight the diverse biological roles of tsRNAs, which involve direct binding to target proteins, formation of complexes for intracellular transport, and regulation of posttranslational modifications.…”
Section: Biological Roles Of Tsrnasmentioning
confidence: 99%
“…These complexes are then transported to the nucleus, enhancing the interaction between EEF1A1 and the MDM2 proto-oncogene (MDM2), ultimately promoting GC progression [ 49 ]. Additionally, Zhao et al [ 50 ] found that the upregulated tRF-Tyr in laryngeal squamous cell carcinoma enhances tumor progression by binding with lactate dehydrogenase A (LDHA), affecting its phosphorylation and leading to increased lactic acid accumulation [ 50 ]. These studies highlight the diverse biological roles of tsRNAs, which involve direct binding to target proteins, formation of complexes for intracellular transport, and regulation of posttranslational modifications.…”
Section: Biological Roles Of Tsrnasmentioning
confidence: 99%